EFEITO DO CIGARRO NOS TECIDOS MOLES, DUROS E NA EFICÁCIA DO CLAREAMENTO DENTAL - Geus, Juliana Larocca de (2016)
The aim of this study was to clinically evaluate the longevity of tooth whitening in smokers, quantify nicotine in teeth exposed to cigarette smoke, as well as evaluate the genotoxic effect of cigarettes through the micronucleus frequency. For this study were conducted four studies. In studies 1 and 2, sixty patients, thirty smokers and thirty nonsmokers, were submitted to at-home bleaching with carbamide peroxide (CP) 10% for three hours daily during three weeks. The color was assessed using the Vita Easyshade spectrophotometer, and shade guides Vita classical organized by value and Vita Bleachedguide D-MASTER, after 12 and 30 months of bleaching, before and after dental prophylaxis. In study 3, sixty-nine teeth were exposed to smoke of 400 cigarettes (positive control). In one group, the dental prophylaxis was performed and, in another, the in-office leaching with hydrogen peroxide (HP) 35%. The color was evaluated initially, after exposure to cigarette smoke, and after dental prophylaxis or in-office bleaching. The teeth of each group were analyzed by gas chromatography and mass spectrometry in order to measure the amount of nicotine in each group. The study 4 consisted of a systematic review that evaluated the frequency of micronuclei in smokers and nonsmokers. Data from studies 1 and 2 showed that for both groups, the main factor was statistically significant (p <0.001). An effective bleaching was observed in both groups at 12 months after dental prophylaxis, however, a dental darkening was observed after 30 months for both groups. In study 3, the amount of nicotine was higher in the positive control group (3.3 ± 1.3 mg / g of tooth), then the prophylaxis group (2.1 ± 1.4 mg / g) and bleaching group (0.8 ± 0.3 mg / g). There was a visually perceptible dental darkening in all groups exposed to cigarette smoke (p <0.001). In the study 4 was a significant difference in the frequency of micronuclei in smokers compared to nonsmokers, however the Chi2 test showed high heterogeneity in the methodology of the assessed studies (p <0.00001). It can be concluded that the bleaching with 10% CP was stable in both groups at 12 months, while the extrinsic stains of diet and smoking were removed by dental prophylaxis, which did not occur in the evaluation of 30 months. Cigarette smoke penetrates in the tooth structure, however the dental prophylaxis and bleaching with PH 35% removed partially the nicotine of tooth. A higher frequency of micronuclei in exfoliated cells of smokers was found in comparison with non-smokers.